An Analysis of India’s “Strategic Autonomy” through the Lens of Triangular Relationship Theory - Tu zhiming (Pacific International Journal, 2026)
Based on Dittmer's triangular theory, India's "strategic autonomy" is essentially a process of seeking balance within multiple, overlapping triangular interactions, yet it gets into a systemic dilemma under the structural pressures of these triangular relationships. Specifically, in the China-Pakistan-India triangle, the close links between China and Pakistan create structural constraints on India, forcing it to devote strategic resources to coping while reinforcing its dependence on external actors to reverse unfavorable situations. In the China-U.S.-India triangle, India's approach of "aligning with the U.S. to contain China" leads to strategic vacillation due to the limited security cooperation and political trust offered by the U.S., coupled with India's emphasis on "strategic autonomy." In the China-Russia-India triangle, the coexistence of Russia-India cooperation and China-Russia strategic collaboration forms a complex games within multiple agendas. Russia’s strategic "turning to the East" and the deepening China-Russia collaboration weaken India’s utility in leveraging Russia to balance China. These triangles are not isolated but interconnected. India’s "alignment with the U.S. against China" triggers Russia’s distrust toward India, while its excessive reactions to China-Pakistan dynamics strengthen its strategic dependence on the U.S. and Russia. Furthermore, the interplay between India’s insufficient intrinsic capabilities and external systemic pressures traps it in the paradox of "strategic autonomy": the more it seeks balance, the deeper its dependence becomes.